Biological properties of equine herpesvirus type 1 DNA: transfectivity and transforming capacity. - Allen, G P (1978)
DNA extracted from purified virions of equine herpesvirus type 1 (EHV-1) was examined for its transfectivity and transforming ability. The infectivity of the herpesvirus DNA was demonstrated by addition of calcium phosphate-DNA coprecipitates to monolayers of permissive horse cells, with resultant plaque formation. The efficiency of transfection (50 to 100 plaque-forming units/microgram of DNA) was reduced by treatment of the viral DNA with deoxyribonuclease or sonication but not with Pronase or antivirus neutralizing serum. When nonpermissive mouse 3T3 Cells lacking the enzyme thymidine kinase (TK-) were transfected with intact EHV-1 DNA, clones of cells transformed to the TK+ phenotype were isolated in selective HAT medium (hypoxanthine, aminopterin, thymidine), which prevents growth of the TK- parental phenotype. The efficiency of transformation ranged from one to five transformants per microgram of EHV-1 DNA. The TK activity of the biochemically transformed cells was characterized by biochemical, electrophoretic, and immunological techniques. By these criteria, the TK activity was identical to the EHV-1 TK and different from the host wild-type enzyme. In contrast to the parental TK+ 3T3 cells, the EHV-1-transformed TK+ cells were unable to grow in the presence of arabinosylthymine, a drug selectively phosphorylated by herpesvirus TKs. These results indicate that stable transfer of EHV-1 genes into nonpermissive cells can be achieved with purified viral DNA.